The Influence of Financial Literacy and Brand Image on Online Shopping Consumptive Behavior on TikTok Platform with Purchase Decision as a Mediator - Fira Isma Ariyanti; Muhammad Fahmi Johan Syah (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to examine the influence of financial literacy and brand image on consumptive behavior in TikTok Shop, with purchase decision as a mediating variable. This research employs a quantitative approach using a correlational design with Structural Equation Modeling (SEM) analysis, utilizing Smart PLS version 3.0 software. Data collection was conducted through questionnaires. The sample consisted of 113 students from Universitas Muhammadiyah Surakarta who actively use TikTok Shop. The findings indicate that financial literacy and brand image significantly influence consumptive behavior. However, financial literacy does not affect purchase decision as a mediator, whereas brand image has a significant impact on purchase decision.